Hydro-environmental characterization of the Rio do Peixe Water Resources Management Unit - Souza, Vanessa Lima de; Américo-Pinheiro , Juliana Heloisa Pinê; Delgado, Maria Isabel (ANAP Brazil, 2025)
ABSTRACTObjective: This study presents the hydroenvironmental characterization of the Peixe River Water Resources Management Unit (UGRHI-21), located in western São Paulo State.Methodology: Using an integrated approach, the physical, environmental, and socioeconomic aspects that influence the dynamics of water resources in the region are analyzed. The study encompasses hydrography, geology, climate, land use, vegetation cover, water quality, and water management structure.Relevance: The hydroenvironmental characterization of this Unit is essential to support planning and land use strategies that reconcile environmental conservation and sustainable regional development, considering the territory's natural and socioeconomic specificities.Results: The results indicate that, despite significant surface and groundwater availability, the unit faces challenges related to water quality and anthropogenic pressure resulting from agricultural expansion, urbanization, and the lack of universal sanitation coverage. Theoretical/methodological contributions: The adoption of integrated management, ecological restoration, and governance strengthening strategies is recommended, aiming to balance socioeconomic development with the water and ecological sustainability of the Rio do Peixe basin.Social and environmental contributions: The work of the Aguapeí and Peixe River Basin Committee (CBH-AP), as well as the implementation of the State Water Resources Plan guidelines, are essential to ensuring sustainable water use and the conservation of the region's aquatic ecosystems. The study reinforces the importance of hydroenvironmental characterization as a technical and strategic tool for environmental planning and integrated water resource management.
Keywords: Environmental management; Vulnerability